Analysis of Reskilling, Upskilling, and Continuous Learning Culture on Adaptability of Hospitality Employees in West Java - Kalsum, ER Ummi; Budiman Djatisara, Ronny Regawa; Novitasari, Salwa Aulia (Westscience Press, 2025)
The adaptability of employees in the hospitality industry is crucial for maintaining service quality and operational efficiency in an evolving market. This study examines the impact of Reskilling, Upskilling, and Continuous Learning Culture on Adaptability among hospitality employees in West Java using a quantitative approach, with data collected from 150 hospitality employees through a Likert scale (1-5) questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The results indicate that Continuous Learning Culture has the strongest influence on Adaptability, followed by Upskilling and Reskilling, suggesting that fostering a continuous learning culture within organizations significantly enhances employees’ ability to adapt to changes, while Reskilling, though still impactful, plays a comparatively smaller role. This study contributes to the literature by demonstrating that sustained learning engagement is a stronger predictor of adaptability than isolated training initiatives and provides managerial recommendations for developing structured learning environments to improve workforce agility in the hospitality sector.